The Role of Job Insecurity, Workplace Bullying, and Work”“Family Conflict on Turnover Intention - Maryam, Resti Siti; -Muhdiyanto, Muhdiyanto; Pramesti, Diesyana Ajeng (Borobudur Management Review, 2025)
Turnover intention is a significant issue for all companies. The purpose of this study is to examine and analyze the influence of job insecurity, workplace bullying, and work-family conflict on turnover intention. This study uses the Social Exchange Theory approach. The population in this study was all employees of Bank BMT BIMA in the Magelang area. A sample of 102 employees was taken using non-probability sampling with a saturated sampling technique. The analysis tool used was multiple linear regression. The results showed that job insecurity and work-family conflict had no effect on turnover intention. Furthermore, workplace bullying had a positive effect on turnover intention. This study presents the discussion in depth.